Aesthetic tissue augmentation with an association of synthetic biomaterial and L-PRF (Research, Society and Development, 2020)
Rehabilitation with osseointegrated implants is a therapeutic option consolidated in the literature and has a high rate of success and predictability. However, the loss of dental elements leads to tissue collapse that often make the installation of dental implants unfeasible, causing atrophic defects in the jaws of varying magnitudes. The objective of this case report was to demonstrate the association of a synthetic biomaterial with Fibrin Rich in Platelets (LPRF) with the purpose of gingival tissue augmentation in aesthetic area. The patient underwent preoperative, clinical and radiographic examinations (Cone Beam computed tomography) of the maxilla region with the making of a prototype and one year and four months of follow-up. A homogeneous onlay graft was performed with a cortico-medullary block in the region of the bone defect. After seven months of bone remodeling, the patient underwent a new computed tomography and dental implants were inserted, concomitant with grafting of particulate biomaterial of inorganic mineral hydroxyapatite, which received an association of L-PRF in liquid phase and was later covered with the L-PRF membrane. After six months, a new computed tomography scan was performed to evaluate the previous procedure and followed with the reopening and placement of provisionals with the conditioning of the gingival tissue. After 3 months, personalized molding was performed and the fixed metal-ceramic prosthesis was made in the region of elements 12 to 22. We can conclude with the clinical case that grafting synthetic biomaterial associated with L-PRF proved to be an effective technique in increasing tissue volume.